TEACHING QUALITY IMPROVEMENT THROUGH “SIULIN” - Hartatik Hartatik (Yayasan Education and Social Center, 2023)
The exam is one of the curriculum implementation activities, which is part of the evaluation of learning activities. A midterm and final semester exam learning system is implemented in one of the integrated Islamic elementary schools in East Java. In contrast, currently, the exam is carried out manually on paper. It could be more efficient, especially with the use of paper. Besides that, the teachers will add working hours to correct exam results. An online exam application design is needed that can help teachers in the online exam process and corrections. The fundamental objective of this research is to create a website-based online exam information system at an integrated Islamic elementary school in one of the cities in East Java. The research method is descriptive qualitative to find facts and original information. Data collection techniques for information system development are used using observations, interviews, and literature studies. While the development method used is the waterfall method. The results of this study are that it can make it easier for teachers to carry out the process of evaluating, correcting, saving teacher time in correcting exam answers, helping teachers to recapitulate grades, reducing the impact of cheating during exams, reducing paper use and making it easier for students to see exam scores